Genotyping of fimbrial adhesins in Escherichia coli strains isolated from Slovak piglets suffering from diarrhea - Vu-Khac, H; Holoda, E; Majerciak, M; Gaspar, G; Pilipcinec, E (Folia microbiologica, 2004)
One-hundred sixty Escherichia coli isolates obtained from piglets with diarrhea from different parts of Slovakia were examined for the presence of genes coding for F4, F5, F6 and F41 fimbrial adhesins, and hemolytic activity. According to polymerase chain reaction tests 74 (46%) E. coli isolates were positive for primers that detected genes coding for fimbrial adhesins. Of these 74 isolates, 64 were positive for genes encoding for F4+, four for F5+, five for F6+, and one for both F41+ and F5+ adhesins.
Keywords: bakteriální adheziny; Animals; Genotype; Escherichia coli Infections; infekce vyvolané Escherichia coli; antigeny bakteriální; Escherichia coli; polymerázová řetězová reakce; Polymerase Chain Reaction; Bacterial Toxins; DNA bakterií; Adhesins, Escherichia coli; DNA, Bacterial; Slovakia; Hemolysin Proteins; genotyp; hemolyziny; prasata; Swine Diseases; proteiny z Escherichia coli; průjem; nemoci prasat; Swine; Diarrhea; Antigens, Bacterial; bakteriální toxiny; Slovenská republika; adheziny Escherichia coli; zvířata; Adhesins, Bacterial; Escherichia coli Proteins